Effects of powder particle size on mechanostructure and cell viability of the synthesised bioceramic bone grafts - Demirel, Mehtap; Aksakal, Bunyamin (KOREAN ASSOC CRYSTAL GROWTH, INC, 2018)
Hydroxyapatite (HA) based biografts were syntesized at 0.68, 1.2 and 2.4 mu m powder particle size by sol gel method. The effect of powder particle sizes on morphology, mechanical properties and in vitro cell viability of the biografts were analysed. Each composition at different particle sizes (0.68, 1.2 and 2.4 mu m) were sintered at 1180 degrees C and quantitative phase analysis was characterized by FTIR, XRD and SEM-EDX. Mechanical properties were determined by axial compression and Vickers hardness tests. The highest compresion strengths and hardness values were obtained in samples having the particle size of 0.68 mu m and such values were increased with decreased particle sizes. Furthermore, from in vitro Cell viability tests it was determined that no toxicity was detected at 0,1 and 0,3 mu M concentrations at lower powder particle sizes. However, cell viability was significantly reduced in the syntesized samples having 2.4 mu m particle size at 0,3 mu M concentration.
Keywords: Biograft; Hydroxyapatite; Mechanical properties; Cell viability; SOL-GEL SYNTHESIS; CALCIUM-PHOSPHATE; HYDROTHERMAL SYNTHESIS; MECHANICAL-PROPERTIES; COATINGS; Materials Science